WAWASAN IBU MENYUSUI TENTANG STUNTING DI WILAYAH KERJA UPT PUSKESMAS PENGALIHAN KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Yulia Febrianita; Putri Wulandini (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
Stunting can be interpreted as a condition of failing to grow in toddlers due to chronic malnutrition so that the child becomes too short for his age. Not to be initiated in early lactation, failure of the exclusive feeding of mothers (BREAST milk), and the early ageing process can be one of the factors of stunting. The purpose of this research is to figure out the insights of breastfeeding mothers about stunting in the working area of Enok in the Sub District Health center of Indragiri Hilir. This type of research is descriptive. The population in this study is all mothers breastfeeding in the working area of the Enok redirecting Puskesmas for 102 people. Samples used as much as 81 nursing mothers. The Samapel retrieval technique is with random samples. Research instruments using questionnaires. The obtained Data is processed manually and presented in a table Form. The results of the study gained 41 respondents (50.62%) Have less insights of stunting. Then deduced insights of mothers breastfeeding in the working area OF UPT Health care of Enok less. Recommended to the community especially nursing mothers should diligently seek information from both electronic media and by participating in health counseling activities.